(untitled) (Kathmandu University Medical Journal, 2022)
Background Type 2 diabetes is an escalating health problem in Nepal and it holds a strong bidirectional Inter relationship with periodontitis. However, lack of its knowledge and motivation among patients may deteriorate and complicate their condition. Objective To assess knowledge among general population regarding the relation between diabetes and periodontitis and to evaluate the role of dentists and physicians in suggesting the diabetic patients for oral health care. Method A cross-sectional study was conducted among the patients visiting Department of Periodontics, Gandaki Medical College. A total 422 patients were interviewed using a set of pretested questionnaire and at the end they were counselled about the impact of diabetes mellitus on periodontal status and vice versa. Result Majority of the patients 257 (60.9%) had no idea about the interrelation between periodontitis and diabetes mellitus. Almost all the patients 363 (86.02%) assumed that poor oral health cannot increase the risk of developing diabetes and amongst those who had knowledge about this relation, the major source of information was their diabetic friends and relatives 46 (10.9%) and other sources such as syllabus 46 (10.9%). Only handful of patients 30 (7.10%) were informed about the relation by their dentist. Ironically, none of them were provided information about the interrelation by their treating physician. Conclusion Overall, only few participants had knowledge about the bidirectional relation between periodontitis and diabetes. Hence, our findings support the greater need for more targeted and specific health education along with close collaboration between dentists and physicians.